2012
DOI: 10.1124/jpet.112.198242
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiplatelet Activity of Protocatechuic Acid through the Inhibition of High Shear Stress-Induced Platelet Aggregation

Abstract: Bleeding is the most common and serious adverse effect of currently available antiplatelet drugs. Many efforts are being made to develop novel antithrombotic agents without bleeding risks. Shear stress-induced platelet aggregation (SIPA), which occurs under abnormally high shear stress, plays a crucial role in the development of arterial thrombotic diseases. Here, we demonstrate that protocatechuic acid (PCA), a bioactive phytochemical from Lonicera (honeysuckle) flowers, selectively and potently inhibits high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…Stumpf et al (29) reported that PCA significantly inhibited TNF-a-induced expression and release of adhesion molecules, cytokines, and chemokines as well as ADP-induced expression of platelet P-selectin in human vascular endothelial cells. A recent study also demonstrated that the anti-platelet and anti-thrombotic effect of PCA is mediated by selectively inhibiting shear-induced platelet aggregation through the blockade of the interaction between von Willebrand factor (vWF) and platelet receptor GPIb (5). Consistent with these studies, our data showed that PCA could also inhibit the inflammatory response and the enhanced platelet aggregation in MI/R.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Stumpf et al (29) reported that PCA significantly inhibited TNF-a-induced expression and release of adhesion molecules, cytokines, and chemokines as well as ADP-induced expression of platelet P-selectin in human vascular endothelial cells. A recent study also demonstrated that the anti-platelet and anti-thrombotic effect of PCA is mediated by selectively inhibiting shear-induced platelet aggregation through the blockade of the interaction between von Willebrand factor (vWF) and platelet receptor GPIb (5). Consistent with these studies, our data showed that PCA could also inhibit the inflammatory response and the enhanced platelet aggregation in MI/R.…”
Section: Discussionsupporting
confidence: 80%
“…Protocatechuic acid (3, 4-dihydroxybenzoic acid, PCA; Fig. 1), a simple phenolic compound, is plentiful in edible fruits and vegetables and also naturally present in many Chinese herbs such as Salvia miltiorrhiza (3), Sarcandra glabra (4), Lonicera japonica (5), and Hibiscus sabdariffa (6), etc. However, over the past years, little attention has been paid to the beneficial effects of PCA on health.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, this bioactive phytochemical was unable to alter platelet aggregation in response to classical platelet agonists like collagen or Thr, although its effect on ADP-induced aggregation remains controversial [33,43]. Additionally, current evidence supports its beneficial antioxidant effects in endothelial and smooth muscle cells [83], leading to propose this molecule as a possible therapeutic candidate for the treatment of thrombosis and other vascular pathologies, like stroke [31].…”
Section: Discussionmentioning
confidence: 92%
“…F u r t h e r m o r e , i t h a s b e e n r e p o r t e d t h a t protocatechuic acid is able to reduce platelet aggregation in response to shear stress, since it reduces the von Willebran factor-dependent stimulation of platelets by blocking the glycoprotein Ib, which would avoid platelet interaction with the endothelium, and subsequently, it would also reduce the positive feedback exerted by von Willebrand factor in recruiting the surrounding circulating platelets [33]. By contrast, this bioactive phytochemical was unable to alter platelet aggregation in response to classical platelet agonists like collagen or Thr, although its effect on ADP-induced aggregation remains controversial [33,43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation